Contribution of autophagy to antiviral immunity. Issue 22 (20th August 2015) - Rey-Jurado, Emma; Riedel, Claudia A.; González, Pablo A.; Bueno, Susan M.; Kalergis, Alexis M.
Abstract : Although identified in the 1960's, interest in autophagy has significantly increased in the past decade with notable research efforts oriented at understanding as to how this multi‐protein complex operates and is regulated. Autophagy is commonly defined as a "self‐eating" process evolved by eukaryotic cells to recycle senescent organelles and expired proteins, which is significantly increased during cellular stress responses. In addition, autophagy can also play important roles during human diseases, such as cancer, neurodegenerative and autoimmune disorders. Furthermore, novel findings suggest that autophagy contributes to the host defense against microbial infections. In this article, we review the role of macroautophagy in antiviral immune responses and discuss molecular mechanisms evolved by viral pathogens to evade this process. A role for autophagy as an effector mechanism used both, by innate and adaptive immunity is also discussed.